2008
DOI: 10.1084/jem.20081427
|View full text |Cite
|
Sign up to set email alerts
|

Control of the adaptive response of the heart to stress via the Notch1 receptor pathway

Abstract: Abbreviations used: BNP, brain natriuretic peptide; CPC, cardiac precursor cell; Hes, Hairy/ enhancer of split; MZB, marginal zone B; Sca, stem cell antigen.A. Croquelois, A.A. Domenighetti, and M. Nemir contributed equally to this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
93
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 47 publications
2
93
2
Order By: Relevance
“…In addition, reactivation of Moreover, results reflecting our data were described by Ma et al who revealed that NICD3 and Hey1 are upregulated after 5-fluorouracil induced injury of the rat tracheal epithelium (144). It is also known that Notch1 plays a major role in the control of the adaptive response of the heart to stress conditions (139) and is activated during liver regeneration (141), further confirming a possible involvement of the Notch pathway in pathomechasim of lung fibrosis.…”
Section: Reactivation Of the Notch Signaling Pathway In Lung Fibrosissupporting
confidence: 76%
See 1 more Smart Citation
“…In addition, reactivation of Moreover, results reflecting our data were described by Ma et al who revealed that NICD3 and Hey1 are upregulated after 5-fluorouracil induced injury of the rat tracheal epithelium (144). It is also known that Notch1 plays a major role in the control of the adaptive response of the heart to stress conditions (139) and is activated during liver regeneration (141), further confirming a possible involvement of the Notch pathway in pathomechasim of lung fibrosis.…”
Section: Reactivation Of the Notch Signaling Pathway In Lung Fibrosissupporting
confidence: 76%
“…The rationale for examining the Notch pathway in lung fibrosis does not exclusively stem from the knowledge of the influence of Notch on the regenerative response to injury in adult tissue (129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141) but also from a growing number of studies showing that Notch signaling may play a significant role in the process of fibrosis in organs such as kidney, skin and heart (95,98,142). In addition, reactivation of Moreover, results reflecting our data were described by Ma et al who revealed that NICD3 and Hey1 are upregulated after 5-fluorouracil induced injury of the rat tracheal epithelium (144).…”
Section: Reactivation Of the Notch Signaling Pathway In Lung Fibrosismentioning
confidence: 99%
“…6,9,12 On the contrary, inhibition of Notch1 signaling exacerbates cardiac hypertrophy, fibrosis, apoptosis, and dysfunction. 9 This evidence raises the possibility that ARBs might attenuate cardiac hypertrophy in a DLL4/ Notch1-dependent manner.…”
Section: Introductionmentioning
confidence: 96%
“…[6][7][8] Notch1 receptor has been speculated to exert cardioprotection in injured myocardium, by controlling the cardiac adaptation to stress, enhancing myocyte survival, promoting precursor proliferation, and reducing fibrosis. 6,[9][10][11] DLL4/Notch1 activation is a requisite for the survival of hypertrophic myocardium and for the regeneration of damaged tissue. 6,9,12 On the contrary, inhibition of Notch1 signaling exacerbates cardiac hypertrophy, fibrosis, apoptosis, and dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation